ANALYSIS OF THE GENETIC EXPRESSION OF COLON CANCER GENETIC BIOMARKERS ON INFLAMMATORY BOWEL DISEASE ON BLOOD AND BIOPSY SAMPLES. (26th January 2023) - Martinez, Evelyn Calderon; Zevallos-Delgado, Christian; Joseph, Maria
Abstract: INTRODUCTION: Inflammatory bowel disease (IBD) is an immune-mediated inflammatory condition of the gastrointestinal tract. Its incidence rose steadily in the last century and the estimated incidence is approximately 2.5 million in Europe and 1.5 million in North America [1]. This condition can be associated with an increased risk of cardiovascular diseases, infections, and cancer [2] The risk of colorectal cancer (CRC) is approximately 2- to 3-fold higher for IBD patients than in the general population. [2] Malignancies are the second most common cause of mortality after cardiovascular disease in patients with IBD. [3] Several genetic biomarkers have been studied as prognostic factors, such as BRAF, CEACAM5, SMAD4, APC, MLH1 (part of the Microsatellite instability prognosis factors), and KRAS. OBJECTIVE: The aim of this study was to determine the gene expression of CRC genetic biomarkers in IBD patients' peripheral blood and biopsy samples. METHODOLOGY: The gene expression data was retrieved from the Gene Expression Omnibus (peripheral blood: GSE186507 and colon biopsies: GSE193677). This data was submitted by Argmann et al, a study that included healthy control patients (n=243), UC (n=421), and CD (n=243). The biopsy samples were obtained from the ileum, colon, and rectum. Several CRC biomarkers were retrieved from the literature. We compared the expression of these biomarkers between the groups in both, blood samples and the different sites of biopsies using T-test (UC vs control, CD vs control, and UC vs CD). RESULTS: The analysis showed a significant difference in some CRC gene biomarkers between IBD patients and the control group in peripheral blood and the different locations where the biopsies were obtained. MLH1 was more expressed in IBD patients compared with healthy patients in the cecum (CD vs control p=8e-06; CD vs UC p= 0.00046), left colon (CD vs UC p= 0.02), right colon (UC vs control p=0.022; CD vs UC p=0.0053), sigmoid colon (UC vs control p=0.037; CD vs UC p=0.028), and rectum (CD vs control p=5e-10, CD vs UC p= 1.2e-13). In the case of the blood samples, the gene expression of SMAD4 (p = 0.03) CEACAM5 (p= 0.02), KRAS (p= 0.0005), and MLH1 (p= 0.0002) was significantly higher in IBD patients compared with control group.